BEING STUDENTS AND MOTHERS: STORIES OF STRENGTH AND RESILIENCE - Sativa, Refi Aksep (Journal of Innovation Research and Knowledge, 2025)
Abstract: Balancing the dual roles of being a student and a mother presents unique challenges, particularly for graduate students who face demanding academic and personal responsibilities. This study investigated the lived experiences of graduate student mothers, focusing on the challenges they faced and the strategies they employed to navigate their dual roles. The purpose of this study was to gain insight into the difficulties that graduate student mothers face and their coping strategies for ‘balancing’ academic and parenting responsibilities. This study used a narrative-based case study as the research design, recruiting three graduate student mothers from three different universities. Personal narrative and semi structured interviews were used to gather data to provide a more in-depth understanding of the context. This study was intended to shed more light on the challenges that graduate student mothers encounter, with the hope that others interested in pursuing higher studies can learn from the participants' stories and consider their experiences before making the "big commitment" of entering academia. It was also hoped that other stakeholders, such as faculty staff and policymakers, would be able to generate a place for more "mother-friendly" programs.